Investigation of Infiltration via Multi-Physics Simulation Tool with Realistic Microstructure Properties. (13th April 2015) - Yang, Tao; Celik, Ismail Bektas; Sezer, Hayri; Lee, Shiwoo; Gerdes, Kirk
Abstract : Infiltration is a potential method to improve the performance of SOFCs. The purpose of this study is to investigate the effects of infiltration via multi-physics simulation tools with realistic microstructure properties. The physics-based simulation tool is developed to extract the properties of fuel cells based on the measured polarization curves and impedance behavior for different fuel/air utilization cases, which has been verified in our previous work. Furthermore, we incorporate the microstructure properties distribution within the electrodes of realistic SOFC. These structural properties are either obtained from experiments (e.g. volume fraction) or calculated based on percolation theory (e.g. interface area, length of triple phase boundary, etc.). In this study, we apply the previously developed simulation tool to analyze both the baseline button cell and the one with infiltrated cathode. The performances of both cells are predicted with the multi-physics numerical simulation and compared against experimental data. In addition, the performances of baseline cell and cathode-infiltrated cell with working loads are predicted. Finally, the properties of both cells are extracted and compared to show the effects of infiltration. The results will help us better understand and improve the infiltration processes.